Cell Behaviors during Closure of the Choroid Fissure in the Developing Eye - Gestri, Gaia; Bazin-Lopez, Naiara; Scholes, Clarissa; Wilson, Stephen W. (Frontiers in Cellular Neuroscience, 2018)
Coloboma is a defect in the morphogenesis of the eye that is a consequence of failure of choroid fissure fusion. It is among the most common congenital defects in humans and can significantly impact vision. However, very little is known about the cellular mechanisms that regulate choroid fissure closure. Using high-resolution confocal imaging of the zebrafish optic cup, we find that apico-basal polarity is re-modelled in cells lining the fissure in proximal to distal and inner to outer gradients during fusion. This process is accompanied by cell proliferation, displacement of vasculature and contact between cells lining the choroid fissure and periocular mesenchyme (POM). To investigate the role of POM cells in closure of the fissure, we transplanted optic vesicles onto the yolk, allowing them to develop in a situation where they are depleted of POM. The choroid fissure forms normally in ectopic eyes but fusion fails in this condition, despite timely apposition of the nasal and temporal lips of the retina. This study resolves some of the cell behaviours underlying choroid fissure fusion and supports a role for POM in choroid fissure fusion.